Short-Term Treatment with Bisphenol-A Leads to Metabolic Abnormalities in Adult Male Mice - Batista, Thiago M.; Alonso-Magdalena, Paloma; Vieira, Elaine; Amaral, Maria Esmeria C.; Cederroth, Christopher R.; Nef, Serge; Quesada, Ivan; Carneiro, Everardo M.; Nadal, Angel (PLOS ONE, 2012)
Bisphenol-A (BPA) is one of the most widespread endocrine disrupting chemicals (EDC) used as the base compound in the manufacture of polycarbonate plastics. Although evidence points to consider exposure to BPA as a risk factor for insulin resistance, its actions on whole body metabolism and on insulin-sensitive tissues are still unclear. The aim of the present work was to study the effects of low doses of BPA in insulin-sensitive peripheral tissues and whole body metabolism in adult mice. Adult mice were treated with subcutaneous injection of 100 µg/kg BPA or vehicle for 8 days. Whole body energy homeostasis was assessed with in vivo indirect calorimetry. Insulin signaling assays were conducted by western blot analysis. Mice treated with BPA were insulin resistant and had increased glucose-stimulated insulin release. BPA-treated mice had decreased food intake, lower body temperature and locomotor activity compared to control. In skeletal muscle, insulin-stimulated tyrosine phosphorylation of the insulin receptor β subunit was impaired in BPA-treated mice. This impairment was associated with a reduced insulin-stimulated Akt phosphorylation in the Thr308 residue. Both skeletal muscle and liver displayed an upregulation of IRS-1 protein by BPA. The mitogen-activated protein kinase (MAPK) signaling pathway was also impaired in the skeletal muscle from BPA-treated mice. In the liver, BPA effects were of lesser intensity with decreased insulin-stimulated tyrosine phosphorylation of the insulin receptor β subunit. In conclusion, short-term treatment with low doses of BPA slows down whole body energy metabolism and disrupts insulin signaling in peripheral tissues. Thus, our findings support the notion that BPA can be considered a risk factor for the development of type 2 diabetes.